Elemental and phase analysis of nanocomposite coatings on basis Ti-Hf-Si-N system received by the vacuum-arc deposition method - Grudnitskiy, V.V.; Beresnev, V.M.; Drobyshevskaya, А.А.; Turbin, P.V.; Toryanik, I.N.; Grankin, S.S.; Kolesnikov, D.А.; Nemchenko, U.S. (Физическая инженерия поверхности, 2012)
Coatings on the basis Ti-Hf-Si-N system were synthesized by vacuum-arc deposition method from
the uniflow and separated ion-plasma flow. The morphology, elemental and phase composition of
coatings were investigated. The dependence of the characteristics of the coating from the physical
and technological parameters of deposition was installed. The two-phase structure of the coating: a
substitutional solution (Ti, Hf)N and quasiamorphous silikonitrid α-Si₃N₄ was determined. The factors
that determine the compressive stresses in the coatings were considered. Методом вакуумно-дугового осаждения из прямоточного и сепарированного ионно-плазменного
потока синтезированы покрытия на основе системы Ti-Hf-Si-N. Исследована морфология,
определен элементный и фазовый состав покрытий. Установлена зависимость характеристик покрытий от физико-технологических параметров осаждения. Определена двухфазная структура покрытия: твердый раствор замещения (Ti, Hf)N и квазиаморфный силиконитрид α-Si₃N₄. Рассмотрены факторы, определяющие сжимающие напряжения в покрытиях. Методом вакуумно-дугового осадження з прямоточного і сепарованого іонно-плазмового потоку синтезовані покриття на основі системи Ti-Hf-Si-N. Досліджено морфологію, визначено елементний і фазовий склад покриттів. Встановлено залежність характеристик покриттів від фізико-технологічних параметрів осадження. Визначена двофазна структура покриття: твердий розчин заміщення (Ti, Hf) N і квазіаморфний силіконітрид α-Si₃N₄. Розглянуто чинники, що визначають стискаючі напруження у покриттях.